2021
DOI: 10.1002/jia2.25701
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial evaluating combination detection of HIV in Malawian sexually transmitted infections clinics

Abstract: IntroductionHIV diagnosis is the necessary first step towards HIV care initiation, yet many persons living with HIV (PLWH) remain undiagnosed. Employing multiple HIV testing strategies in tandem could increase HIV detection and promote linkage to care. We aimed to assess an intervention to improve HIV detection within socio‐sexual networks of PLWH in two sexually transmitted infections (STI) clinics in Lilongwe, Malawi.MethodsWe conducted a randomized controlled trial to evaluate an intervention combining acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
0
11
1
Order By: Relevance
“…Our research revealed potential areas for optimizing IT services in Ukraine, including promotion of provider-assisted notification to increase HIV testing and case detection, a finding substantiated by the literature. A meta-analysis comprising over 5,000 patients in both high resource and resource limited settings found that provider-assisted partner services resulted in a 1.5-fold increase in HIV testing over passive referral by clients [ 26 ], and a recent randomized trial in Malawi that compared social network testing using contract notification to passive client referral found a 1.9-fold increase in HIV case finding [ 27 ]. Despite the demonstrated benefits of provider-assisted notification, however, our data showed that ICs chose provider-assisted notification less than 25% of the time, suggesting that additional intervention or education for both providers and ICs on the benefits of provider-assisted notification may improve HIV testing and case detection.…”
Section: Discussionmentioning
confidence: 99%
“…Our research revealed potential areas for optimizing IT services in Ukraine, including promotion of provider-assisted notification to increase HIV testing and case detection, a finding substantiated by the literature. A meta-analysis comprising over 5,000 patients in both high resource and resource limited settings found that provider-assisted partner services resulted in a 1.5-fold increase in HIV testing over passive referral by clients [ 26 ], and a recent randomized trial in Malawi that compared social network testing using contract notification to passive client referral found a 1.9-fold increase in HIV case finding [ 27 ]. Despite the demonstrated benefits of provider-assisted notification, however, our data showed that ICs chose provider-assisted notification less than 25% of the time, suggesting that additional intervention or education for both providers and ICs on the benefits of provider-assisted notification may improve HIV testing and case detection.…”
Section: Discussionmentioning
confidence: 99%
“…The overall HIV prevalence among adults aged 15–64 years in Malawi is 10.6%, and 11.5% in the Lilongwe city 23. The HIV prevalence among patients with STI in Malawi is around 18.0%–22.0%15 24 and around 13.3% at Bwaila STI clinic 25…”
Section: Methods and Analysismentioning
confidence: 99%
“…23 The HIV prevalence among patients with STI in Malawi is around 18.0%-22.0% 15 24 and around 13.3% at Bwaila STI clinic. 25…”
Section: Study Settingmentioning
confidence: 99%
“…In a randomized controlled trial (RCT) among PWH at 2 sexually transmitted infection (STI) clinics in Malawi, 20 we previously demonstrated that a combination intervention of cPN, social contact referral, and AHI screening increased the rate of new HIV diagnoses within participants' sociosexual networks compared with pPN alone (standard of care). However, cPN and the successful identification of persons with AHI require available staff and enhanced testing services, which can be resource-intensive.…”
Section: Introductionmentioning
confidence: 99%